Three Perspectives on Older Adults’ Daily Performance, Health, and Technology Use During COVID-19: Focus Group Study - Cohen Elimelech, Ortal; Rosenblum, Sara; Tsadok-Cohen, Michal; Meyer, Sonya; Ferrante, Simona; Demeter, Naor (JMIR aging, 2024)
During COVID-19 lockdowns, older adults' engagement in daily activities was severely affected, causing negative physical and mental health implications. Technology flourished as a means of performing daily activities in this complex situation; however, older adults often struggled to effectively use these opportunities. Despite the important role of older adults' social environments-including their families and health professionals-in influencing their technology use, research into their unique perspectives is lacking. This study aimed to explore the daily activity performance, health, and technology use experiences of healthy independent Israeli adults (aged ≥65 years) during COVID-19 from a 3-dimensional perspective: older adults, older adults' family members, and health professionals. Nine online focus groups, averaging 6-7 participants per group, were conducted with older adults, family members, and health professionals (N=59). Data were analyzed using thematic analysis and constant comparative methods. The intertwining of daily activity performance and health emerged as a central theme, with differences between the groups. Older adults prioritized their self-fulfilling routines based on motivation and choice, especially in social-familial activities. In contrast, family members and health professionals focused on serious physical and mental health COVID-19-related consequences. A consensus among all three groups revealed the meaningful role of technology use during this period in bridging functional limitations. Participants delved into technology's transformative power, focusing on the need for technology to get engaged in daily activities. This study illustrates the profound interplay between daily activity performances, physical and mental health, and technology use, using a 3-dimensional approach. Its focus on technology's uses and benefits sheds light on what older adults need to increase their technology use. Interventions for improving digital activity performance can be tailored to meet older adults' needs and preferences by focusing on motivational and preference-related activities.